Phosphorylation of Intrinsically Disordered Regions in Remorin Proteins - Marín, Macarena; Ott, Thomas (Frontiers in Plant Science, 2012)
Plant-specific remorin proteins reside in subdomains of plasma membranes, originally termed membrane rafts. They probably facilitate cellular signal transduction by direct interaction with signaling proteins such as receptor-like kinases and may dynamically modulate their lateral segregation within plasma membranes. Recent evidence suggests such functions of remorins during plant–microbe interactions and innate immune responses, where differential phosphorylation of some of these proteins has been described to be dependent on the perception of the microbe-associated molecular pattern (MAMP) flg22 and the presence of the NBS–LRR resistance protein RPM1. A number of specifically phosphorylated residues in their highly variable and intrinsically disordered N-terminal regions have been identified. Sequence diversity of these evolutionary distinct domains suggests that remorins may serve a wide range of biological functions. Here, we describe patterns and features of intrinsic disorder in remorin protein and discuss possible functional implications of phosphorylation within these rapidly evolving domains.